Vera wong's unsolicited advice for murderers ebook - Sutanto, Jesse Q. (Vera Wong, 2023)
A USA Today bestseller Edgar Award Winner for Best Original Paperback Audie Award Winner for Mystery Libby Award Winner for Best Mystery A lonely shopkeeper takes it upon herself to solve a murder in the most peculiar way in this captivating mystery by Jesse Q. Sutanto, bestselling author of Dial A for Aunties. Vera Wong is a lonely little old lady—ah, lady of a certain age—who lives above her forgotten tea shop in the middle of San Francisco’s Chinatown. Despite living alone, Vera is not needy, oh no. She likes nothing more than sipping on a good cup of Wulong and doing some healthy detective work on the Internet about what her Gen-Z son is up to. Then one morning, Vera trudges downstairs to find a curious thing—a dead man in the middle of her tea shop. In his outstretched hand, a flash drive. Vera doesn’t know what comes over her, but after calling the cops like any good citizen would, she sort of . . . swipes the flash drive from the body and tucks it safely into the pocket of her apron. Why? Because Vera is sure she would do a better job than the police possibly could, because nobody sniffs out a wrongdoing quite like a suspicious Chinese mother with time on her hands. Vera knows the killer will be back for the flash drive; all she has to do is watch the increasing number of customers at her shop and figure out which one among them is the killer. What Vera does not expect is to form friendships with her customers and start to care for each and every one of them. As a protective mother hen, will she end up having to give one of her newfound chicks to the police?